2018
DOI: 10.1002/cne.24534
|View full text |Cite
|
Sign up to set email alerts
|

Full: Ontogenesis and development of the nonhuman primate pulvinar

Abstract: Recent evidence demonstrates that the pulvinar nuclei play a critical role in shaping the connectivity and function of the multiple cortical areas they connect. Surprisingly, however, little is known about the development of this area, the largest corpus of the thalamic nuclei, which go on to occupy 40% of the adult thalamus in the human. It was proposed that the nonhuman primate and the human pulvinar develop according to very different processes, with a greatly reduced neurogenic period in nonhuman primate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…In this context, Homman‐Ludiye and colleagues recently identified in the embryonic mouse dorsal thalamus, cell clusters expressing genes specifically enriched in the neonatal marmoset PM (Homman‐Ludiye et al. ), suggesting that the origin of the PM could be traced back beyond the primate lineage.…”
Section: Origin Of the Pmmentioning
confidence: 99%
See 3 more Smart Citations
“…In this context, Homman‐Ludiye and colleagues recently identified in the embryonic mouse dorsal thalamus, cell clusters expressing genes specifically enriched in the neonatal marmoset PM (Homman‐Ludiye et al. ), suggesting that the origin of the PM could be traced back beyond the primate lineage.…”
Section: Origin Of the Pmmentioning
confidence: 99%
“…However, a recent study in the marmoset monkey ( C. jacchus ) demonstrated that pulvinar neurones are still being generated a few days before birth (Homman‐Ludiye et al. ), suggesting that ontogenesis of the pulvinar is more similar across primates than originally believed. Despite pulvinar neurogenesis spanning the entire period of brain development in the marmoset, there is no evidence of a second telencephalic wave of neurones.…”
Section: Origin Of the Pmmentioning
confidence: 99%
See 2 more Smart Citations
“…Nissl and Acetylcholine-esterase staining protocols were performed on slide-mounted sections as previously described (Homman-Ludiye et al, 2018).…”
Section: Histological Stainingmentioning
confidence: 99%